Spillover effects of taxes on government debt: a spatial panel approach. (3rd May 2016) - Kopczewska, Katarzyna; Kudła, Janusz; Walczyk, Konrad; Kruszewski, Robert; Kocia, Agata
ABSTRACT: It is claimed that tax policy is neither time- nor space-independent due to cross-border tax base mobility, which induces spillovers. Specifically, fiscal shocks in one country are supposed to have an impact on fiscal policies in other countries. Different types of taxes influence economies differently. This paper addresses the question of their impact on government debt. Within a framework of spatial econometric modeling, we evaluate the impact of capital, labor and consumption taxes on public debt in 34 European countries in 2002–2011, and find strong spatial spillovers. We show that a consumption tax and, to a lesser degree, a capital tax significantly affect the sovereign debt, and that the global relations play a leading role (i.e. dominate the local ones) in shaping fiscal policy.